Pythagorean Neutrosophic IUP-Algebras: Theoretical Foundations and Extensions (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces the concepts of Pythagorean neutrosophic IUP-subalgebras, Pythagorean neutrosophic IUP-ideals, Pythagorean neutrosophic IUP-filters, and Pythagorean neutrosophic strong IUP-ideals within the framework of IUP-algebras. We establish the fundamental properties of these structures and provide necessary and sufficient conditions under which a Pythagorean neutrosophic set qualifies as one of these algebraic subsets. Additionally, we explore the relationships between these subsets and their corresponding level subsets, offering a deeper understanding of their interconnections. By extending the theoretical foundation of IUP-algebras through the integration of Pythagorean neutrosophic sets, this study contributes to the broader field of algebraic structures and uncertainty modeling. Beyond its theoretical significance, this work promotes inclusive and equitable education by making abstract mathematical concepts more accessible to students, educators, and researchers at both the school and university levels. By fostering mathematical literacy and critical thinking, this research equips learners with essential problem-solving skills applicable to various fields, including mathematics, computer science, and artificial intelligence. To enhance accessibility, key concepts are presented in a structured and comprehensible manner, allowing students from diverse backgrounds to engage with complex algebraic theories more effectively. The insights gained from this study can be incorporated into school curricula, providing foundational knowledge that supports further academic exploration. Moreover, this research contributes to developing a learning environment that encourages curiosity, logical reasoning, and interdisciplinary connections, ensuring that students and educators have the necessary resources to explore, understand, and apply advanced mathematical theories in real-world contexts. Ultimately, this study fosters lifelong learning and innovation by strengthening the integration of mathematical education across different learning environments.